2020
DOI: 10.3390/cancers12010160
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Tumor Cells as a Marker of Disseminated Disease in Patients with Newly Diagnosed High-Risk Prostate Cancer

Abstract: The aim of this study was to investigate whether the enumeration of circulating tumor cells (CTCs) in blood can differentiate between true localized and metastatic prostate cancer. A cross-sectional study of 104 prostate cancer patients with newly diagnosed high-risk prostate cancer was conducted. In total, 19 patients presented metastatic disease and 85 were diagnosed with localized disease. Analyses included intergroup comparison of CTC counts, determined using the CellSearch® system, EPISPOT assay and GILUP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 56 publications
2
26
0
1
Order By: Relevance
“…[13][14][15][16][17] Moreover, using CellCollector, the detection rate in patients in early cancer stages is more than 50%, 20% higher than the detection rate of the similar product CellSearch. 16,18,19 The high detection rate in early-stage tumors maybe facilitates research on the application of CTCs in the diagnosis of early-stage cancer. A study by He et al reported CTCs detection rate of 15.6% (5/32) in patients with ground-glass nodules and mutations in cancer-related genes, including KIT, SMARCBI, and AP53, in all CTCs-positive patients.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16][17] Moreover, using CellCollector, the detection rate in patients in early cancer stages is more than 50%, 20% higher than the detection rate of the similar product CellSearch. 16,18,19 The high detection rate in early-stage tumors maybe facilitates research on the application of CTCs in the diagnosis of early-stage cancer. A study by He et al reported CTCs detection rate of 15.6% (5/32) in patients with ground-glass nodules and mutations in cancer-related genes, including KIT, SMARCBI, and AP53, in all CTCs-positive patients.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome this problem, several approaches have been described, such as ultrasensitive sequencing of ctDNA and in-vivo enrichment of CTCs, boosting the sensitivity in general, or including tumor-derived extracellular vesicles as they are more abundant than CTCs [ 21 , 22 , 23 , 24 ]. Most importantly, several research articles show that liquid biopsy analytes can complement each other instead of simply being redundant [ 25 , 26 , 27 ]. This opens the possibility of combining liquid biopsy analytes to increase overall sensitivity for tumor-relevant information, leading to a higher proportion of informative patient blood samples.…”
Section: Discussionmentioning
confidence: 99%
“…It is placed directly in the torrent A patient's blood through an indwelling catheter (size = 20 G), remains in the vein of the arm for 30 min and allows the capture of CTCs in vivo since the system is in contact with a high volume of blood. The catheter is lined with anti-EpCAM antibody and subsequently allows the characterization of CTCs (immunofluorescence, protein analysis, RT-qPCR, FISH, sequencing, analysis of expression and cell culture) [40,41]. While being safe and easy to use, the CellCollector ® did not outperform CellSearch ® in terms of CTCs yield or sensitivity.…”
Section: Methods: Isolation Identification and Culturementioning
confidence: 99%
“…For CellCollector ® , the sensitivity and specificity of the in vivo CTC detection strategy for the diagnosis of early-stage lung cancer were 52.94% and 90%, respectively [41]. In addition, for CellCollector ® , although the sensitivity of CTC detection needs to be further increased, may suggest that high CTC counts might contribute to the identification of high-risk prostate cancer patients with occult metastases at the time of diagnosis [40].…”
Section: Methods: Isolation Identification and Culturementioning
confidence: 99%